IDENTIFICATION AND ANALYSIS OF HUMAN ACTIONS IN CASE OF SGTR INITIATING EVENT - Rahman, K. U.; Arshad, N.; Z. Arif, H. M.; Habib, U.; Kanwal, S. (The Nucleus, 2020)
Identification and modeling of human actions, from safety point of view is an important part of human reliability analysis of Probabilistic Safety Assessment (PSA). In case of SGTR, human actions have significant effect on the safety and radioactive releases. The human actions, isolation of defective steam generator (IFSG), pressure balance between primary and secondary side (OAPB) and reactor cool down and depressurization (OACD) were modeled and analyzed in this study. Probabilities associated with these human actions were estimated using Standardized Plant Analysis Risk associated with Human (SPAR-H) with generic data. HEPs are 0.0564, 0.0952 and 0.1059 for IFSG, OAPB and OACD respectively. Human error probabilities were the major contributors to core damage frequency of SGTR.